2008
DOI: 10.1038/gene.2008.61
|View full text |Cite
|
Sign up to set email alerts
|

A novel transcript of mouse interleukin-20 receptor acts on glomerular mesangial cells as an aggravating factor in lupus nephritis

Abstract: We identified a novel soluble protein, mouse (m)IL-20R1a, generated by alternative splicing of the mIL-20R1 gene, which encodes one subunit of the receptor complex for mIL-19, mIL-20 and mIL-24. mIL-20R1a has 77.14% amino-acid identity with the extracellular domain of mIL-20R1. However, no significant interaction between mIL-20R1a and mIL-19 or mIL-20 was detected. Consequently, we aimed to clarify whether mIL-20R1a might function as a novel effector on certain cells. Competitive binding assays demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…Although not all mIL-20R1a transgenic mice developed renal calcium deposition, these mice could still serve as a useful model for studies not only on kidney stones but also on lupus nephritis. 23 We found other pathological changes in procreation and hematopoiesis in these transgenic mice (data not shown). Further studies are necessary to clarify whether mIL-20R1a is involved in the pathophysiological events that underlie procreation-or hematopoiesis-related diseases.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Although not all mIL-20R1a transgenic mice developed renal calcium deposition, these mice could still serve as a useful model for studies not only on kidney stones but also on lupus nephritis. 23 We found other pathological changes in procreation and hematopoiesis in these transgenic mice (data not shown). Further studies are necessary to clarify whether mIL-20R1a is involved in the pathophysiological events that underlie procreation-or hematopoiesis-related diseases.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, elevated mIL-20R1a in splenocytes of SLE-prone mice promoted stimulated splenic B cells to produce more IL-10. 23 The in vitro study showed the possible biological roles of mIL-20R1a in lupus nephritis. 23 Besides exploring the involvement of mIL-20R1a in the pathogenesis of lupus nephritis, we also sought to investigate the in vivo function of mIL-20R1a.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations